Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 1 - Some Basic Concepts of Arithmetic and Algebra - 1.5 - Use of Properties - Problem Set 1.5 - Page 34: 68



Work Step by Step

We substitute $n=10$ in the given expression and evaluate it using order of operations (PEDMAS): $-(n+2)-3(n-6)$ =$-(10+2)-3(10-6)$ =$-(12)-3(4)$ =$-(12)-12$ =$-24$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.